Every Camp Has a Story: Barrier Free Youth Camp with Teacher Narratives - Yilmaz, Atike; Koç, Serdar; Akaydin, Şevval; Han, Mustafa (Nevzat Demirci, 2023)
This study was carried out to investigate the opinions of teachers who participated in the youth camp without disabilities organized for individuals with intellectual disabilities. The research was conducted in twelve teachers who participated in the barrier-free youth camp organized in Mersin province Silifke district and were selected through easily accessible situation sampling. Data were collected by means of personal information forms created by the researchers together with semi structured interview questions, while the content analysis method was used for data analysis. Five main themes and ten sub themes, dependent on the former, emerged from the findings. The expectations of the participating teachers before the camp started were determined to contribute to the socialization of the students, and their expectations regarding the camp environment were positive. Relating their experiences during the camp, the teachers stated that the activities prepared for the students were organized according to the latters’ characteristics, with enriched and well-developed content. Although the camp was suitable for students with intellectual disabilities in terms of accessibility, they reported that there was no canteen in the camp to meet their daily needs. They found the camp to be beneficial for students to integrate, socialize and act independently After the camp had finished, the teachers expressed their satisfaction with the experience, concluding that it had been productive both for their professional development and for the students. However, they suggested increasing the duration and number of the camps and simplifying the arrival and departure procedures. © The Author(s) 2023.
Keywords: Barrier Free Youth Camp; Opinion; Teacher